2021
DOI: 10.1111/amet.13028
|View full text |Cite
|
Sign up to set email alerts
|

Ontologies of climate change

Abstract: In Namibia, both Damara pastoralists (ǂNūkhoen) and scientists agree that it rains less frequently than before. To explain their observations, however, scientists refer to carbon dioxide molecules, while the pastoralists point to social tensions, neoliberalism, and failures of the postcolonial state. To understand this discrepancy, I ask whether what scientists call precipitation and what Damara call ǀnanus are really the same thing. Engaging with phenomenological theories, I propose a worldliness continuum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…To explain this, I have identified three components that can become building blocks for a more finished phenomenological theory of environmental knowing. They add to my previous work that foregrounds practices, aims, and the networks of involvements around a phenomenon (Schnegg 2019(Schnegg , 2021a. The remaining paragraphs reflect these components and the steps still ahead.…”
Section: Ontological Polyphonymentioning
confidence: 89%
See 3 more Smart Citations
“…To explain this, I have identified three components that can become building blocks for a more finished phenomenological theory of environmental knowing. They add to my previous work that foregrounds practices, aims, and the networks of involvements around a phenomenon (Schnegg 2019(Schnegg , 2021a. The remaining paragraphs reflect these components and the steps still ahead.…”
Section: Ontological Polyphonymentioning
confidence: 89%
“…Friedrich (2017, 331) finds that on the Philippine island of Palawan, people with different education levels disagree on climate change. In a similar vein, my past research in Namibia has shown how pastoralists and scientists make distinctively different sense of the lack of rain and of climate change (Schnegg 2019(Schnegg , 2021a.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, scholars probed the “ontological” premises of climate change, interrogating the either/or of the “one‐world‐many‐representations model and the many‐worlds model,” instead proposing a worldliness continuum “along which ontological difference varies” (Schnegg 2021, 269).…”
Section: IIImentioning
confidence: 99%